PROGRAM PELATIHAN PEMBUATAN ALAT PERAGA MATEMATIKA YANG INTERAKTIF BAGI GURU SD SE-GUGUS 01 KECAMATAN PUNGGING - Ririn Febriyanti; Slamet Boediono; Esty Saraswati NH (Prodi. Pendidikan Matematika, FKIP, Universitas Riau, 2019)
The training program for making mathematics teaching aids held at SDN Kembangringgit 2, Kembangringgit village, Pungging district, Mojokerto regency. Generally, this training aims to increase creativity and students’ enthusiasm for learning mathematics. The main objectives of this training are (1) to establish good relations with schools, (2) to make optimal use of mathematics teaching aids, (3) to provide training on how to make mathematics teaching aids and increase comprehension in mathematics by using mathematics teaching aids. While the target of this mathematics teaching aids training were teachers of elementary school in district of Pungging, Mojokerto regency. The approach used when delivering training matter was the discovery. In discovery approach, student find how to solve the problem themselves. While the methods that we used are lecture, discussion, and demonstration. The advice in this article is teachers should develop their abilities and understanding related to the development and application of teaching aids continuously.